PENGARUH KEPERCAYAAN SISWA PADA MATEMATIKATERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - AMINULLAH AMINULLAH (GANEC SWARA, 2019)
This study aims to describe the effect of student confidence in mathematics on students' mathematical problem solving abilities. This type of research is a quasiexperimental study and the sample in this study is a class XI student majoring in hotel accommodation with 31 students. Retrieval of data using questionnaire and test instruments. The results of this study obtained the average student confidence in mathematics at 60.23 with a standard deviation of 3.66. While the mathematical problem solving abilities of students obtained an average of 66.94 with a standard deviation of 9.63. Students 'trust in mathematics and students' mathematical problem solving abilities are quite sufficient. There is an influence of students 'trust in mathematics on students' mathematical problem solving abilities indicated by F count (4,746) ≥ F table (4,18) or significance number at 0,038 ≤ 0.05 ANOVA. The magnitude of the influence of student confidence in mathematics on students' mathematical problem solving abilities is 14.1%. The regression equation obtained by Y ̂ = 7.455 + 0.988X + ϵ. This means that if the value of student confidence in mathematics is 1 unit, then the value of the predictive variable will increase by 0.988. The higher the confidence of students in mathematics, the mathematical problem solving abilities of students will also increase.